Sizable retrograde transtubal leakage of saline during bipolar hysteroscopic myomectomy: A potential cause of hypoxia: Retrograde transtubal leakage of saline during surgery - Darwish, Atef; Zubeydi , Leyla; Darwish , Dina; Dervis, Vefa; Mohamed , Fathi F; ElKhatib , Mohamed L (Journal of Surgery and Medicine, 2025)
This case report discusses a bipolar hysteroscopic myomectomy procedure for a type II FIGO submucous myoma using 0.9% saline as a distension medium. Following the successful excision of the myoma, a significant decrease in oxygen saturation was observed, confirmed by blood gas analysis, urgent X-ray, and echocardiography. Despite the absence of acidosis or pulmonary edema, emergency abdominal ultrasonography revealed a large volume of intraperitoneal fluid. Approximately one liter of intraperitoneal saline was drained during an emergency laparoscopic intervention, leading to a notable improvement in the patient’s hypoxia. This case highlights the importance of considering retrograde transtubal leakage of saline as a potential cause of intraoperative hypoxia, particularly in patients undergoing advanced hysteroscopic procedures with suspected patent fallopian tubes.